2021
DOI: 10.1161/jaha.120.020631
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Angiogenic Markers in Pregnant Women With Chronic Hypertension

Abstract: Background Women with chronic hypertension face a 5‐ to 6‐fold increased risk of developing preeclampsia compared with normotensive women. Angiogenic markers, especially soluble fms‐like kinase 1 (sFlt‐1) and placental growth factor (PlGF), were identified as clinically useful markers predicting the development of preeclampsia, but data on the prediction of superimposed preeclampsia are scarce. Therefore, we aimed to evaluate the predictive value of the sFlt‐1/PlGF ratio for delivery because of sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…[74][75][76][77] sFlt-1 and PlGF tests are also useful in distinguishing preeclampsia from other confounding diseases such as gestational hypertension, primary renal disease, chronic hypertension, gestational thrombocytopenia, and immune thrombocytopenic purpura. 61,75,76,[78][79][80][81][82][83][84] By specifically identifying preeclampsia, the test can enable earlier diagnosis and targeted treatments.…”
Section: Aid In the Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…[74][75][76][77] sFlt-1 and PlGF tests are also useful in distinguishing preeclampsia from other confounding diseases such as gestational hypertension, primary renal disease, chronic hypertension, gestational thrombocytopenia, and immune thrombocytopenic purpura. 61,75,76,[78][79][80][81][82][83][84] By specifically identifying preeclampsia, the test can enable earlier diagnosis and targeted treatments.…”
Section: Aid In the Diagnosismentioning
confidence: 99%
“…72,88,94,102 Several other studies have confirmed the robust predictive performance of these biomarkers. 84,89,[103][104][105][106][107][108][109][110][111][112] Although there was growing evidence that angiogenic biomarkers could also be useful to predict disease progression in a diverse group of patients with suspected preeclampsia 89,[113][114][115][116][117] and in patients hospitalized with a hypertensive disorder of pregnancy, 118 studies in developing countries have been limited. 114 The PRAECIS study (NCT03815110)-among the largest and the most diverse U.S. studies to date with 18 participating centers-analyzed ~1000 pregnant women hospitalized with a hypertensive disorder between 23 and 35 weeks' gestation.…”
Section: Aid In Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, maternal serum angiogenic marker imbalance has been acknowledged in several international guidelines as a criterion for diagnosis of PE. Moreover, the maternal serum sFlt-1/PlGF ratio has been shown to be an important tool, not only for the diagnosis of PE in women with suspected PE, but also in the prognosis of the disease; for example, estimating the time until delivery and prediction of adverse maternal and perinatal outcome 2,3,6,7,18,36,40 . Repeat assessment of the ratio is advised in women with suspected PE, with a ratio between 38 and 85 or 110 after 34 weeks' gestation, as well as for the surveillance of high-risk cohorts, such as women with chronic hypertension 7,32 .…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…It remains one of the leading causes of maternal and perinatal morbidity and mortality worldwide 1 . Recently, angiogenic marker assessment has revolutionized the prediction and diagnosis of hypertensive disorders of pregnancy [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and has been recommended as a useful tool in several international guidelines [19][20][21] . Compared with conventional diagnostic methods, such as blood pressure measurement and assessment of proteinuria, angiogenic markers show superior predictive accuracy for adverse outcome in pregnancy complicated by PE 15,[22][23][24][25][26][27][28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%